Analysis: Married Women-Segmented Module Meet Doctor Users With Low Interest in The Klikdokter App - Isfan Ferli; Fidy Rachman Osthar; Rama Rizqullah Fahrizal; Jerry Heikal (Lembaga Pengembangan Kinerja Dosen, 2024)
The clinic's process for requesting a consultation with a doctor and receiving a queue number is inefficient. To help patients make the most of their time at the clinic, it is helpful to provide them with information on when physicians will be available to see them. A new approach to health development governance is required under Regulation No. 21 of 2020 of the Republic of Indonesia's Minister of Health, which addresses the Ministry's Strategic Plan for 2020–2024. This plan encompasses health information systems, research integration, and development, among other areas. First, Health Technology Transformation, which includes developing and integrating health data; second, Health Service Application Integration and Development; and third, Health Technology Ecosystem Development, will house the primary activities involved in health technology transformation. This study's findings suggest that consumers are mostly interested in finding hospitals in close proximity to their homes, rather than using the doctor's appointment component of the KlikDokter app. Because of this, KlikDokter has to implement a change movement that can increase the number of health facilities that operate with Klik Doctor, allowing it to reach the closest health facility. It also has to link insurance and BPJS so that health facilities may provide transaction features.